Morphological Characterization of Mango (Mangifera indica) in Situbondo (International Forum of Researchers and Lecturers, 2024)
Situbondo is a district in the province of East Java, Indonesia. Situbondo is a mango production center, in 2019, based on BPS East Java data, produced mango fruit reaching 23,511.70 tons. This research is basic research to determine the potential of mangoes as a food diversification and energy diversification product in Situbondo. This research will be able to determine the morphological characterization of mango types in Situbondo region. By knowing the morphological characteristics of each type of mango, it can be determined which types of mango have the potential to be used as food diversification products or energy diversification products. This research was conducted in 17 sub-districts in Situbondo Regency. Characterization of mango fruit from various types of varieties was carried out using the 2006 IPGRI (International Plant Genetic Research Institute) mango series as a reference. 5 different types of mango were found, namely: Gadung mango, Manalagi mango, Arum manis mango, Arum merah mango and Garifta mango. There is a diversity of mango plant morphology found in terms of tree morphology, leaf morphology and fruit morphology. Arum manis mango and Arum merah mango have almost the same characteristics. Gadung mango has the largest tree shape among other mangoes.